Reproducibility of Areal Topography Parameters Obtained by Atomic Force Microscope - Andrej Razumić; Biserka Runje; Zdenka Keran; Zvonko Trzun; Daniel Pugar (Tehnički Glasnik)
In the context of quality management and Industry 5.0, reproducibility is a critical indicator of the ability to achieve consistent and predictable results in laboratories, research, as well as in systems and processes. Reproducibility is also an indispensable component of measurement uncertainty, which quantifies the precision of measurement results. To standardize the measurement procedure for surface topography parameters obtained using atomic force microscope (AFM) and to establish the accuracy and precision of measurement results, an analysis of repeatability and reproducibility was conducted in accordance with the ISO 5725-2:2019 standard, Accuracy (trueness and precision) of measurement methods and results – Part 2: Basic method for the determination of repeatability and reproducibility of a standard measurement method. Measurements were performed on two AFM standards and a steel sample. The research was conducted over the course of one year and repeated after four years using the same samples.